إمكانية تطبيق إشراف العمل المعرفي من وجهة نظر المشرفين التربويين بمنطقة الحدود الشمالية - الرويلي، سعود بن جبيب الطرقي (جامعة الأزهر - كلية التربية, 2021)
هدفت هذه الدراسة إلى الكـشـف عـن إمكانية تطبيق إشراف العمل المعرفي من وجهة نظر المشرفين التربويين بمنطقـة الحـدود الـشمالية، وتكونـت عينـة الدراسـة مـن (97) مـشـرفاً، واستخدم الباحث المنهج الوصفي من خلال استبانتين من إعداده، واحدة للتعرف على إمكانية تطبيق اشراف العمل المعرفي، والثانية لمعوقات تطبيقه، وأظهرت النتائج وجود إمكانية لتطبيق إشراف العمل المعرفي بدرجة مرتفعة بشكل عام، وقد حازت أربعة مجالات بإمكانية تطبيق بدرجة مرتفعة هي (دعم رؤية المعلم، التنفيذ، الأساليب، المعرفة) فيما حاز مجال (دعم الأداء الفردي للمعلم) على إمكانية تطبيق بدرجة متوسطة، وأشارت نتائج الدراسة إلى عدم وجـود فروق دالة إحصائياً تبعاً لمتغيرات (المؤهل، التخصص، سنوات الخبرة)، كما أشارت النتائج إلى وجود ثلاثة معوقات لإمكانية تطبيق اشراف العمل المعرفي تمثلت في (ازدحام جدول المشرف التربوي بالأعمال التقليدية، وضعف قناعة القيادة العليا، وتصورات المعلمين السلبية تجاه العمل الاشرافي).
The study aimed to explore the possibility of administering the knowledge work supervisions. Ninety-seven (97) supervisors participated in this study. The descriptive method was adopted making use of two questionnaires developed by the researcher. The questionnaires were used to identify the possibility of administering the knowledge work supervision and the obstacles of their application. The results showed that in general there is a high possibility of applying the knowledge work supervision. Such skills can be administered to a high degree in four domains, namely teacher's vision, implementation, methods and knowledge. The other domain (the individual teacher's performance support) can be applied to a smaller extent. In addition, the results revealed that there were no significant differences in the following variables (qualification, specialization, years of experience). The results also showed that there were three obstacles that hinder the possible application of the knowledge work supervision. These obstacles included the overload of the educational supervisor's schedule with traditional work, the weakness of the conviction of the senior leadership, and the teachers' negative perceptions towards supervisory work.
Keywords: الإشراف التربوي -- اقتصاديات المعرفة -- القيادات التربوية -- الإدارة التعليمية